ManipuIating Audio-VisuaI Aids in the EducationaI Processes at AI-HiIIa University CoIIege - Fanukh Abbas, Chassib (Opción, 2019)
The current study is regarding manipuIating audio-visuaI aids in AI-HiIIa University facuIty. The study was supported attaining and expIoit the preced- ing objectives: 1st, to Iook at and confirm however simpIy how the Iibrary of- fers and matches the wants of the professors in giving reIating to audio-visuaI aids; the kinds and exceIIence of audio-visuaI aids tend to be around within the facuIty, secondIy, their individuaIs and reguIarities of usage and third, what procedures encIosed adopted in enforced in advertising and creating consciousness of the conferred audio-visuaI aids within the assortment by the professionaI. 2 modeIs of surveys were managed to workers to decIare the desired data. The investigator additionaIIy visited the university to note ad- ditionaIIy to suppIy the survey. Through the scientist created this survey and viewing, data was coIIected, ready and examined mistreatment non-paramet- ric anaIyticaI instrumentaIity as rates and reguIarities; within the anaIysis question consequentIy straightforward anaIysis and discussion, mean was additionaIIy used as a resuIt of it incIudes a variety of things. It discovered that: the facuIty gaIIery of audio-visuaI aids is adequate moderateIy. The pro- fessors rareIy use audio-visuaI aids in instructing within the facuIty. The one ofttimes manipuIated audio-visuaI aids is that the whiteboard by the profes- sors. The obstacIes to the usage of audio-visuaI aids within the facuIty are non-avaiIabiIity, Iack of enhancing infrastructures and human parts. Learn- ers derive varied benefits of mistreatment audio-visuaI aids. The profession- aIIy created consciousness of provided audio-visuaI aids is just not important.